Respon inflamasi pulpa gigi tikus Sprague Dawley setelah aplikasi bahan etsa ethylene diamine tetraacetic acid 19% dan asam fosfat 37% - Nadie Fatimatuzzahro; Tetiana Haniastuti; Juni Handajani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Etching agents such as ethylene diamine tetraacetic acid (EDTA) and phosphoric acid which are widely used in adhesive restoration system, are aimed to increase retention of restorative materials; however, these agents may induce inflammation of dental pulp. The major function of the inflammatory response is to remove invading pathogens or damaged tissue/ cells and therefore, initiate repair. Neutrophils and macrophages are motile phagocytes that constitute the body's first line of defense. Purpose: The purpose of the present research was to study the effect of 19% EDTA and 37% phosphoric acid for etching application agents on the inflammatory response of the dental pulp. Methods: Forty-five male Sprague Dawley rats were divided into 3 groups. Cavity preparation was made on the occlusal surface of maxillary first molar using a round diamond bur. Nineteen percent of EDTA, 37% phosphoric acid, and distilled water were applied on the surface of the cavity of the teeth in group I, II and III respectively. The rats were sacrified at 1, 3, 5, 7, and 14 days after the application (n=3 for each day). The specimens were then processed histologically and stained with hematoxylin eosin. Results: ANOVA showed a significant difference (p<0.05) among treatment groups, indicating that etching agents application induced neutrophils, macrophages and lymphocytes infiltration in the dental pulp. Tuckey HSD test showed that application of 37% phosphoric acid increased higher number of neutrophils, macrophages and lymphocytes significantly than 19% EDTA (p<0.05). Conclusion: The study suggested that 37% phosphoric acid induced higher number of the inflammatory cells than 19% EDTA.Latar belakang: Penggunaan bahan etsa seperti ethylene diamine tetraacetic acid (EDTA) dan asam fosfat pada sistem restorasi adhesif bertujuan untuk meningkatkan retensi bagi bahan restorasi, namun penggunaan bahan-bahan tersebut dapat menginduksi inflamasi pada pulpa. Respon inflamasi berfungsi untuk menghilangkan patogen, sel-sel atau jaringan yang rusak dan menginisiasi perbaikan. Netrofil dan makrofag adalah sel fagosit yang merupakan garis pertama pertahanan tubuh. Tujuan: Penelitian ini bertujuan untuk meneliti efek EDTA 19% dan asam fosfat 37% sebagai bahan etsa terhadap respon inflamasi pada pulpa gigi. Metode: Empat puluh lima ekor tikus Sprague Dawley jantan dibagi menjadi 3 kelompok. Permukaan oklusal gigi molar satu rahang atas dipreparasi menggunakan diamond round bur. Pada kelompok I kavitas diaplikasikan EDTA 19%, kelompok II diaplikasikan asam fosfat 37% dan kelompok III diaplikasikan akuades. Hewan coba dikorbankan pada hari ke-1, 3, 5, 7 dan 14 setelah aplikasi bahan etsa (n=3). Spesimen diproses secara histologis dan dicat dengan hematoksilin eosin. Hasil: Hasil ANOVA menunjukkan perbedaan yang bermakna (p<0,05) antar kelompok perlakuan, mengindikasikan bahwa aplikasi bahan etsa menyebabkan infiltrasi sel inflamasi pada pulpa, baik netrofil, makrofag dan limfosit. Hasil uji Tuckey HSD menunjukkan bahwa asam fosfat 37% menstimulasi infiltrasi sel netrofil, makrofag dan limfosit signifikan (p<0,05) lebih banyak dibanding EDTA 19%. Simpulan: Penelitian ini menunjukkan bahwa asam fosfat 37% menyebabkan infiltrasi sel inflamasi yang lebih banyak dibanding EDTA 19%.